Designing a novel tomato ideotype for future cultivation in space manned missions - Pagliarello, Riccardo; Bennici, Elisabetta; Cemmi, Alessia; Di Sarcina, Ilaria; Spelt, Cornelis; Nardi, Luca; Del Fiore, Antonella; De Rossi, Patrizia; Paolini, Francesca; Koes, Ronald; Quattrocchio, Francesca; Benvenuto, Eugenio; et al. (Frontiers in Astronomy and Space Sciences, 2023)
Introduction: Methods for production of fresh, health food are needed in view of long-term, deep-space manned missions. To this end, crops tailored for better performance under non-terrestrial conditions may be obtained by the exploitation of biochemical patterns related to specialized metabolites known to confer protection against environmental challenges and to be beneficial to human health. Methods: In this work, for the first time, MicroTom plants have been engineered specifically for agrospace applications to express PhAN4, a MYB-like transcription factor able to regulate the biosynthesis of anthocyanins that influence tomato genes possibly involved in agrospace-relevant functions. Results:PhAN4 engineering underpinned the genetic background of the dwarf tomato MicroTom while maintaining yield and photosynthetic capacity. PhAN4 expression resulted in the accumulation of anthocyanins and polyphenols, a differential carotenoid profile, increased antioxidant scavenging capacities of fruits compared to the original genotype. Improved ability to counteract ROS generation and to preserve plant protein folding after ex-vivo gamma irradiation was observed. Discussion: These results highlights that the manipulation of specific metabolic pathways is a promising approach to design novel candidate varieties for agrospace applications.